Pengaruh Kualitas Audit, Lingkup Audit Dan Gaya Kepemimpinan Terhadap Efektivitas Pengendalian Internal Di Sektor Pemerintah - Ivand Satria; Mia Angelina Setiawan (Universitas Negeri Padang, 2020)
The study aims to know how to describe and partially test assumptions in the quality of the audit, the scope of the audit, and the leadership style which are proxy with the variables of Independence and, on the Effectiveness of Internal Control in the Government which are analyzed using multiple linear regression. The sampling technique used is quota sampling. The results showed that the quality of the audit did not affect the effectiveness of the internal control. The scope of the audit did not show any effect on the effectiveness of the internal control. And leadership style has an impact on the effectiveness of internal control.